Student Development Aspects Based on Learner Characteristics in Primary Learning Contexts - Darnanengsih; Yuspiani Yuspiani; Alwan Subhan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
Understanding learner characteristics is a crucial foundation for implementing effective and equitable education. Each learner possesses unique differences in potential, learning styles, interests, and socio-cultural backgrounds that influence learning processes and outcomes. This article aims to analyze a characteristic-based approach to developing three major educational aspects: cognitive, affective, and psychomotor domains. Using a qualitative descriptive approach through library research, the study synthesizes relevant literature on learner development. The results indicate that instructional approaches considering learner characteristics enhance learning effectiveness and holistic personal growth. The cognitive aspect relates to thinking and reasoning abilities; the affective aspect involves attitudes, values, and motivation; while the psychomotor aspect pertains to physical and motor coordination skills. These three domains should be developed harmoniously by considering learning styles (visual, auditory, kinesthetic) and individual differences such as talents, interests, and multiple intelligences. The findings imply that teachers and curriculum developers should adapt learning strategies and content to accommodate diverse learner characteristics, particularly in the implementation of the Merdeka Curriculum, to promote inclusive and meaningful learning experiences.